Polysomaty in Cymbidium - Fukai, Seiichi; Hasegawa, Atsushi; Goi, Masanori (HortScience, 2002)
Nuclear DNA content in various parts of Cymbidium plants was measured by flow cytometry. Two types of Cymbidium, protocorm-like body (PLB)-propagated epiphytic hybrids and rhizome-propagated terrestrial C. kanran Makino demonstrated polysomaty. Small shoots on PLBs of Cymbidium hybrids showed two peaks (2C and 4C) while PLBs showed four peaks, estimated to be 2C, 4C, 8C, and 16C. Roots and floral organs excluding ovaries of hybrids were highly polysomatic as were the rhizomes and roots of C. kanran. The patterns of polysomaty development were organ and developmental stage specific. Young leaves taken from in vitro plants are suitable material for determining the ploidy levels of Cymbidium plants by flow cytometry.